Teamwork and Adherence to Guideline on Newborn Resuscitation—Video Review of Neonatal Interdisciplinary Teams - Brogaard, Lise; Hvidman, Lone; Esberg, Gitte; Finer, Neil; Hjorth-Hansen, Kristiane R.; Manser, Tanja; Kierkegaard, Ole; Uldbjerg, Niels; Henriksen, Tine B. (Frontiers in Pediatrics, 2022)
Background: Little is known about the importance of non-technical skills for the adherence to the guidelines, when teams of midwifes, obstetricians, anesthesiologist, and pediatricians resuscitate and support the transition of newborns. Non-technical skills are competences underpinning successful teamwork in healthcare. These are usually referred to as leadership, situational awareness, communication, teamwork, decision making and coping with stress and fatigue. Objective: By review of videos of teams managing newborns with difficult transition, we aimed to investigate whether the level of the teams’ non-technical skills was associated with the degree of adherence to guideline of newborn resuscitation and transitional support at birth. Methods: Four expert raters independently assessed 43 real-life videos of teams managing newborn with transitional difficulties. Exposure was the non-technical score, obtained by the Global Assessment Of Team Performance checklist (GAOTP). GAOTP was rated on a Likert Scale 1-5 (1=poor, 3=average and 5=excellent). The outcome was the clinical performance score of the team assessed according to adherence of the international Liaison Committee on Resuscitation (ILCOR) guideline for neonatal resuscitation and transitional support. The ILCOR guideline was adapted into the checklist TeamOBS-Newborn to facilitate a structured and simple performance assessment (low score 0-60, average 60-84, high 85-100). Interrater agreement was analyzed by intraclass correlation (ICC), Bland-Altman analysis and Cohen´s kappa weighted. Results: Teams with an excellent non-technical score had a relative risk 5.5 (95% confidence interval (CI)2.4-22.5) of high clinical performance score compared to teams with average non-technical score. In addition, we found a doses response like association. The specific non-technical skills associated with the highest degree of adherence to guideline were leadership and teamwork, coping with stress and fatigue and communication with parents. Inter-rater agreement was high; raters assessing non-technical skills achieved an interclass coefficient (ICC) 0.88(95%CI;0.79-0.94); the neonatologists assessing clinical performance achieved an ICC of 0.81(95%CI;0.66-0.89). Conclusion: Teams with an excellent non-technical score had five times the chance of high clinical performance compared to teams with average non-technical skills. High performance teams were characterized by leadership and teamwork, coping with stress and fatigue and communication with parents.